Xuesaitong Soft Capsule (Chinese Patent Medicine) for the Treatment of Unstable Angina Pectoris: A Meta-Analysis and Systematic Review. (30th December 2013) - Yang, Xiaochen; Xiong, Xingjiang; Wang, Heran; Yang, Guoyan; Wang, Jie
Abstract : Objective. To provide a systematic review to evaluate the effectiveness and safety of Xuesaitong soft capsule (XST) in treating unstable angina (UA). Methods. An extensive search of 6 medical databases was performed up to August 2013. Randomized controlled trials (RCTs) involving XST alone or combined with conventional drugs versus conventional drugs were included. A meta-analysis of reduction of angina symptoms and electrocardiogram (ECG) improvement was performed to evaluate the effects of XST on UA. Results. After researching, a total of 6 RCTs with 716 participants were included. Our review showed that XST combined with conventional drugs had significant effect on relieving angina symptoms (RR: 1.14 [ 1.07, 1.22 ] ; P = 0 . 0001 ) and improving ECG (RR: 1.26 [ 1.12, 1.42 ] ; P = 0 . 0001 ) compared with conventional drugs alone. Conclusions. XST appears to have beneficial effects on improvement of ECG, reduction of angina symptoms, and decreasing the frequency and duration of angina attack in participants with UA. However, the findings should be interpreted with caution due to the poor methodological quality of the included trials.